A Bibliometric Analysis on Trends, Directions and Major Players of International Relations Studies - Wahid, Ratnaria; Shukri, Shazwanis; Ahmad, Mohammad Zaki (Universiti Utara Malaysia Press, 2023)
As communications technology, air travel, and a complex international economy continue to make the world smaller, the importance of peaceful and cooperative relationships between nations increases. However, it is unclear to what extent research on international relations (IR) has expanded as a global discipline; narrated by balanced perspectives and provides an impact. This study conducts a bibliometric analysis of 4,986 documents related to IR as recorded in the Scopus database from 1913 to 2022. Specifically, this paper analyzes (a) the trends and developments; (b) influential documents and frequent keywords and (c) major players in terms of productive journals, authors and institutions in IR studies. This paper provides a new panoramic view through tables and science maps on the publication of IR studies. The findings show a gradual interest in the IR field before the Second World War and this accelerated during the mid-twentieth century. Political economy is gaining more importance and most publications centre on IR theories while discussing prevailing events affecting the world. However, the Western influence of IR is still primarily mainstream, where IR publications are mainly controlled by large Western publishers, influenced by Western authors affiliated with long-established Western institutions. Seemingly, the non-Western contributions to the IR field have yet to establish their own footing in the field despite much discussion about diversifying IR. This remains a challenge for non-Western scholars, journal publishers, and institutions seeking to contribute to the ongoing debate in the study of international relations.